Effect of a model-based educational program for mothers, on home-related injury prevention among under-five-year children in rural Twiserkan, Iran - Maryam Afshari; Abbas Moghimbeigi; Seyed Mohammad Mahdi-Hazavehei; Forouzan Rezapur-Shahkolai (The Turkish Journal of Pediatrics)
Children under 5 years of age are most vulnerable in terms of home-related injuries. As a majority of these injuries are predictable and preventable, it is important to design preventive intervention programs that can be utilized as models of health education. The aim of this study was to determine the effect of an educational program, using the PRECEDE model, for rural mothers, on home-related injury prevention among under-five-year old children. This quasi-experimental study was conducted on 72 mothers, with at least one under-five-year old child, in the rural areas of Twiserkan (Toyserkan) County in Iran. The intervention and control groups (36 participants in each), were interviewed in pre/post-test study by trained interviewers, using the questionnaire. The intervention group participated in four educational sessions. The questionnaire included the questions on demographic information, mothers` beliefs and caring in relation to child-injury prevention, based on the PRECEDE model and focusing on predisposing factors (knowledge and attitudes), enabling factors; reinforcing factors; and mothers` preventive behaviors. According to the results of the study, the mean scores of predisposing factors (knowledge), enabling and reinforcing factors and also mothers` behaviors on injury prevention, did not have significant differences between two groups before intervention, whereas they had significant differences after intervention. This study showed that the educational program, using the PRECEDE model, can be effective on promoting knowledge and performances of mothers in relation to home-related injury prevention among their under-five-year old children.